Women’s knowledge of toxoplasmosis infection and basic prevention measures - Wasik, Magdalena Anna (Journal of Education, Health and Sport, 2019)
Introduction: Toxoplasmosis is a disease caused by Toxoplasma gondii protozoan. Toxoplasmosis is particularly dangerous for the foetus and any infection, regardless of the period of pregnancy, may cause disorders in the extra-fetal life. The paper assesses the knowledge of women about toxoplasmosis infection, basic definitions and prophylactic measures. Aim: The aim of the study was to investigate the level of knowledge of women about Toxoplasma gondii infection, as well as the basic preventive actions. Material and method: The study was conducted in the period from February to June 2016 by means of a diagnostic survey. 63 women aged 20 and over took part in the survey. The tool used in the study was a questionnaire. The most numerous group were the respondents aged 20-29 years and the least aged 40-49 years. The research results were developed in Microsoft Excel and Statistica 13.1. Results: The analysis of the collected data shows that women with higher and secondary education have the greatest knowledge of both defining and basic preventive measures. Conclusions: The level of women’s knowledge about Toxoplasma gondii infections varies according to the education of the respondents. The knowledge about basic preventive measures that can significantly reduce the serious consequences of Toxoplasma gondii infections for the developing fetus should be disseminated.